Effect of Short-Term Transcutaneous Vagus Nerve Stimulation (tVNS) on Brain Processing of Food Cues: An Electrophysiological Study - Obst, Martina A.; Heldmann, Marcus; Alicart, Helena; Tittgemeyer, Marc; Münte, Thomas F. (Frontiers in Human Neuroscience, 2020)
Background The vagus nerve plays an important role in the regulation of food intake. Modulating vagal activity via electrical stimulation (VNS) in patients and animal studies caused changes in food intake, energy metabolism, and body weight. However, the moderating impact of cognitive processes on VNS effects on eating behavior, has not been investigated so far. Hypothesis We hypothesized that transcutaneous VNS (tVNS) affects food intake by altering cognitive functions relevant to the processing of food-related information. Methods Using a repeated measurement design, we applied tVNS and a sham stimulation for 2h on two different days in normal-weight subjects. We recorded standard scalp EEG while subjects watched food and object pictures presented in an oddball-task. We analyzed the event-related potentials (ERPs) P1, P2, N2, and LPP, and also examined the amount of consumed food and eating duration in a free-choice test meal. Results Significant differences between stimulations were observed for the P1, P2, and N2 amplitudes. However, we found no tVNS dependent modulation of food intake nor a specific food-related stimulation effect on the ERPs. Further analyses revealed a negative relationship between P2-amplitude and food intake for the sham stimulation. Significant effects are additionally confirmed by Bayesian statistics. Conclusion Our study demonstrates tVNS’ impact on visual processing. Since the effects were similar between food and object stimuli, a general effect on visual perceptual processing can be assumed. More detailed investigations of these effects and their relationship with food intake and metabolism seem reasonable for future studies.